RECENT RESEARCH OF SHEAR CONNECTION IN PREFABRICATED STEEL-CONCRETE COMPOSITE BEAMS - Pavlović, Marko; Spremić, Milan; Marković, Zlatko; Buđevac, Dragan; Veljković, Milan (Journal of Applied Engineering Science, 2014)
Prefabrication of steel-concrete composite decks can improve their competitiveness and sustainability. This paper presents recent studies of longitudinal shear connection at the University of Belgrade, Faculty of Civil Engineering. Grouped welded headed studs and bolted shear connectors, suitable for prefabricated composite construction, has been examined in push-out tests. Totally 30 tests were conducted, and advanced FEA were made using Abaqus/Explicit dynamic solver. Based on the experimental and numerical studies behaviour those two shear connectors are compared.
Keywords: Bolted shear connectors; Grouped headed studs; Prefabricated composite beams